Estudo das tensões em próteses sobre implantes esplintadas: análise pelo método da fotoelasticidade - Villa, Luiz Marcelo Ribeiro [UNESP] (2013)
Purpose: The purpose of this study was to evaluate the influence of different lengths and splinting of implants on stress distribution in implant-supported prostheses under axial and oblique loading by means of the method of photoelasticity. Materials and methods: 05 models in photoelastic resin was prepared with different proposed situations, there were 400 applications for load analysis. Tensions were considered quantitatively and qualitatively using a randomized, single blind method. The reproducibility of the study was assessed using the intra correlation coefficient, systematic error and random error. The analysis of variance to three criteria and post - Tukey tests were used, and p values > 0.05 was adopted to analyze the main differences. Results: The measurements showed a high intra-concordance coefficient (ICC> 0.97). The prosthetic implant splinting acted favorably in the distribution of stresses and strains in the transmission next to the implant (p<0.001) when compared to the unitary prosthesis. The oblique loading was more damaging and potentialized the formation of stresses in adjacent implants (p<0.001). The increase in length was a significant factor for the evaluation of the models B and C (p = 0.004), the model B had a higher concentration of fringes as compared with D and E (p<0.001). Conclusion: The prosthetic implant splinted behaved better biomechanically compared prosthetics unit. The increased length was important in reducing stress. The oblique loading was more detrimental to the stress distribution compared to axial loading.